2015
DOI: 10.1016/j.ecoleng.2015.09.078
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing ecosystem water-use efficiency of croplands with eddy covariance measurements and MODIS products

Abstract: a b s t r a c tHow to quantify the variability in ecosystem water use efficiency (WUE) of croplands is of vital importance. Especially in the context of changing hydrologic environment, much attention need to be paid on how to use limited water to improve crop yield. However, the biophysical performances of environmental/biological controls, crop types, and effects of diverse farming practices on WUE remain unclear. Therefore, this study aims to address these questions through tower-based measurements from edd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
3
12
0
1
Order By: Relevance
“…6, in general, GPP MOD showed a poor agreement whereas ET MOD performed relatively well at the four forest sites except several 8-day periods. Previous studies also confirmed the reliable ET MOD for croplands relying completely on rainfall (Cammalleri et al, 2014;Tang et al, 2015a) and evergreen forests (Liu et al, 2015). The large underestimation of GPP MOD during the vegetation periods may lead to a similar pattern in ecosystem WUE.…”
Section: Uncertainties In Modis Gpp and Et Productssupporting
confidence: 52%
See 1 more Smart Citation
“…6, in general, GPP MOD showed a poor agreement whereas ET MOD performed relatively well at the four forest sites except several 8-day periods. Previous studies also confirmed the reliable ET MOD for croplands relying completely on rainfall (Cammalleri et al, 2014;Tang et al, 2015a) and evergreen forests (Liu et al, 2015). The large underestimation of GPP MOD during the vegetation periods may lead to a similar pattern in ecosystem WUE.…”
Section: Uncertainties In Modis Gpp and Et Productssupporting
confidence: 52%
“…Nevertheless, tower-based observations are spatially limited for adequate sampling of natural ecosystems. The spatiotemporal variability of WUE in large areas has been rarely quantified mainly owing to the complicated interactions between water and carbon as well as the uncertainty in the interactive influences of multiple environmental controls (Tian et al, 2010;Tang et al, 2015a). Although it can be estimated using empirical models driven by highly-related meteorological inputs (Wang et al, 2007;Beer et al, 2009;Yang et al, 2013a), it is worthwhile exploring methods to quantify WUE entirely from remotely sensed information as this could greatly reduce the difficulty in acquiring infrequently meteorological data.…”
Section: Introductionmentioning
confidence: 99%
“…Some reliable remote sensing data on vegetation, such as MODIS products of leaf area index (LAI), gross primary production (GPP), and net primary production (NPP), can be further incorporated to calibrate the model [ Zhu and Zhuang , ]. The observed water flux (evapotranspiration, ET) and latent heat flux (based on the eddy covariance technique) can also be included in the calibration [ Tang et al, ; Trusilova et al , ; Ueyama et al, ]. The ecosystem flux data will help refine model parameters to quantify NEP more precisely on regional scale in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A eficiência do uso da água (WUE) utiliza a relação entre a produtividade primária bruta (PPB) da cultura ou vegetação e a evapotranspiração (ET), já que as trocas de carbono e água entre a vegetação e a atmosfera (fotossíntese), desempenham papel importante no ecossistema (Dalastra et al, 2020;Yamori, 2020). Além de ser uma informação importante utilizada para a avaliação dos impactos referentes as mudanças climáticas, deficiência da irrigação e gestão das estratégias afins de produtividades do ecossistema (Tang et al, 2015a;Tang et al, 2015b).…”
Section: Introductionunclassified